Pemanfaatan Foto Konstruksi untuk Penilaian Keselamatan Kerja pada Pekerjaan Erection Girder - Muhammad Luthfi Asyir Suhaeb (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Work safety is an important aspect in the construction industry, especially in girder erection work that involves high risks due to the installation of large beams and the use of heavy equipment. This study aims to assess the implementation of work safety on the Solo-Yogyakarta-YIA Toll Road construction project by referring to safety standards from the Ministry of Public Works and related regulations. The research data consisted of 28 project photos covering girder erection preparation work, girder erection, and girder bracing. The assessment was conducted by three certified construction OHS experts using a checklist of work safety standards. The results of the Bayes Theorem analysis showed that all girder erection preparation work (7 photos) and girder erection (15 photos) were performed safely with a value of P(H|Ecomb) = 1. On girder bracing work, five out of six photos were rated as safe, while one photo showed unsafe work. This finding indicates that although most of the work has met safety standards, there are still aspects that require improvement. This study recommends a thorough implementation of safety attributes, especially on aspects that have not met the standards, to minimize the risk of occupational accidents on girder erection work in construction projects. This step is important to ensure worker safety and support the creation of a safer work environment.